CaIn2S4 decorated WS2 hybrid for efficient Cr(VI) reduction - Liu, Baibai (2021)
Exploiting efficient visible light active photocatalyst is a great challenge with potential applications such as environmental pollution and solar energy conversion. Herein, a series of CaIn 2 S 4 /WS 2 hybrids was fabricated via a simple hydrothermal method. WS 2 as cocatalyst increases the visible light absorption and separation efficient of charge carrier at the interface, leading to the enhanced photocatalytic activity of CaIn 2 S 4 /WS 2 . CaIn 2 S 4 /20 wt% WS 2 hybrid shows the highest Cr(VI) reduction rate of 98% and methyl orange degradation rate of 96%. This work could offer some thought for designing and fabricating hybrid photocatalyst with high efficient and stable activity.